Synchronization of coupled map lattices - Baraviera, Alexandre (2023)
In this paper we address the issue of synchronization of coupled map lattices, introducing concepts of local and global synchronization for a class of systems that extends the coupled map lattices. A criterion for local synchronization is given; numerical experiments are exhibited to illustrate the criteria and also to raise some questions in the end of the text.